2021
DOI: 10.1039/d0ta10207e
|View full text |Cite
|
Sign up to set email alerts
|

Correlating MOF-808 parameters with mixed-matrix membrane (MMM) CO2 permeation for a more rational MMM development

Abstract: Consistent structure-performance relationships for the design of MOF (metal-organic framework)-based mixed-matrix membranes (MMMs) for gas separation are currently scarce in MMM literature. An important step in establishing such relationships could...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…As previously discussed, rational pairing involves the exploitation of specific attributes of filler materials to complement the limitations of polymer matrices (see Section 5). For example, Thür et al recently found that the CO 2 adsorption enthalpy (Q st ) of MOF-808 gave a stronger correlation to the performance of MMMs as opposed to its intrinsic CO 2 uptake, suggesting a possibility of thoughtful design of MOF-based MMMs by leveraging proven structural-performance indicators [151]. Furthermore, considering that the polymer matrices have a strong influence over the MMM performance (see discussion in Section 5), our group recently attempted to decouple the polymer matrix effect, and proposed a filler enhancement index (F index ) that illuminates the true effectiveness of the filler by considering both permeability and selectivity enhancements for CO 2 /CH 4 separation [44].…”
Section: Discussionmentioning
confidence: 99%
“…As previously discussed, rational pairing involves the exploitation of specific attributes of filler materials to complement the limitations of polymer matrices (see Section 5). For example, Thür et al recently found that the CO 2 adsorption enthalpy (Q st ) of MOF-808 gave a stronger correlation to the performance of MMMs as opposed to its intrinsic CO 2 uptake, suggesting a possibility of thoughtful design of MOF-based MMMs by leveraging proven structural-performance indicators [151]. Furthermore, considering that the polymer matrices have a strong influence over the MMM performance (see discussion in Section 5), our group recently attempted to decouple the polymer matrix effect, and proposed a filler enhancement index (F index ) that illuminates the true effectiveness of the filler by considering both permeability and selectivity enhancements for CO 2 /CH 4 separation [44].…”
Section: Discussionmentioning
confidence: 99%
“…MOF-808 was synthesized as described in our previous study [37]. First, 182 mL H 2 O was used to dissolve 5.08 g (24.2 mmol) BTC and 23.4 g (72.8 mmol) ZrOCl 2 •8H 2 O in a 500 mL round-bottom flask and subsequently 26.8 mL (712 mmol) FA was added.…”
Section: Mof Synthesismentioning
confidence: 99%
“…We have previously investigated the effect of the node-capping modulator in MOF-808 on water sorption and the detoxification of chemical warfare agents, observing significant variance in MOF behavior depending on which modulator was used during synthesis. While the influence of capping group identity on CO 2 sorption in MOF-808 has been probed using postsynthetic substitution reactions, we are not aware of any studies varying the modulator during synthesis for the purpose of investigating CO 2 adsorption mechanisms. Further, MOF-808 has been synthesized using a variety of modulators, making it a promising platform for studying these effects.…”
Section: Introductionmentioning
confidence: 99%